Characteristic differences in barrier and hygroscopic properties between normal and cosmetic dry skin. I. Enhanced barrier analysis with sequential tape‐stripping. (31st January 2014) - Lu, N.; Chandar, P.; Tempesta, D.; Vincent, C.; Bajor, J.; McGuiness, H.
Synopsis Objective Cosmetic dry skin often has a lower hydration level but a similar apparent barrier function, as measured by transepidermal water loss (TEWL), than that of the normal skin. To investigate the intrinsic difference in barrier property and moisture‐holding ability between the cosmetic dry and normal skin, we developed a new clinical and data analysis procedure based on sequential tape‐stripping with TEWL measurement, coupled with chemical analysis for protein and natural moisturizing factors (NMF) in the stratum corneum. Methods A clinical study consisting of 64 healthy Caucasian female subjects with normal and cosmetic dry skin was conducted according to our clinical and data collection protocols. After the baseline visual dryness assessment, 20 tape‐strips were placed and removed on each test site using D‐Squame tapes. TEWL was measured at baseline and after the 5th, 10th, 15th and 20th tape‐strips. All tapes were analysed for protein mass via chemical extraction and the Pierce BCA protein assay, as well as using an infrared densitometry device SquameScan 850A. The stratum corneum thickness and barrier quality (water transport resistance per thickness of the stratum corneum) were decoupled from the apparent barrier function using the TEWL and protein data. Results A linear relationship between 1/TEWL and cumulative protein removal was observed for both normal and cosmetic dry skin. However, the slope of the linear relation was significantly steeper for normal skin, and significantly more protein was removed from cosmetic dry skin. The results showed that on average, the barrier quality of the stratum corneum of the normal skin is about 40% higher than that of the dry skin, whereas the stratum corneum of the dry skin is about 30% thicker than that of the normal skin. In addition, the amount of SC removal in sequential tape‐stripping is generally non‐uniform. Conclusion Our results demonstrated that there are characteristic differences in the barrier property between normal and cosmetic dry skin. In comparison to the normal skin, the stratum corneum of the cosmetic dry skin is considerably thicker, however, with a lower barrier quality. The results also showed that the amount of the SC removal in sequential tape‐stripping is generally non‐uniform. Therefore, the number of tape strips is not a good indicator for the tape‐stripping depth.